(untitled) (Research, Society and Development, 2021)
Introduction: Pre-hospital emergency care is the first specialized aid to reach the victim in traffic accidents, and time is a fundamental response in this type of health problem. This time can undergo significant variations in all its stages. Objective: to analyze the adoption of a resource management software used in emergency relief contributed to improving APH relief vehicles’ dispatch process and, consequently, reducing response time. Methodology: This is an exploratory and descriptive case study, carried out in two stages. In the first stage, a retrospective and cross-sectional study were carried out of the requests for help received by the CBMERJ Emergency Medical Regulation Center in 2018. In the second step, a qualitative evaluation was carried out, through a prospective cross-sectional study through data analysis from the said center, in 2019. Results and Discussion: Secondary data were used, referring to the care of victims of health problems, in the city of Rio de Janeiro, in 2018 and 2019 (n = 69,922) extracted from the database CBMERJ. After data treatment, duplicate, canceled, inconcludent, and TLIAs were removed (n = 31,600). Conclusion: There was an improvement in the time of activation of the response by 50.9%, demonstrating its effectiveness in implementing the tool.